2020
DOI: 10.1016/j.jtho.2020.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Multidisciplinary Management Options for Locally Advanced NSCLC During the Coronavirus Disease 2019 Global Pandemic

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is currently accelerating. Patients with locally advanced NSCLC (LA-NSCLC) may require treatment in locations where resources are limited, and the prevalence of infection is high. Patients with LA-NSCLC frequently present with comorbidities that increase the risk of severe morbidity and mortality from COVID-19. These risks may be further increased by treatments for LA-NSCLC. Although guiding data is scarce, we present an expert thoracic oncology multidisciplinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 75 publications
0
35
0
2
Order By: Relevance
“…Even the recommendations of the Memorial Sloan-Kettering Cancer Center, a well-known supporter of neoadjuvant chemotherapy in selected stage III patients, do not include this indication[ 50 ]. The Fox Chase Cancer Center guidelines comprehensively address the treatment of NSCLC during the COVID-19 pandemic stating “Patients with resectable disease can be treated with definitive non-operative management if surgical resources are limited or the risks of perioperative care are high...”[ 51 ]. Nevertheless, it is essential that the treatment approach be individualised within the parameters set by an interdisciplinary tumour board.…”
Section: Neoadjuvant and Postoperative Radiotherapy In Non-small Cellmentioning
confidence: 99%
“…Even the recommendations of the Memorial Sloan-Kettering Cancer Center, a well-known supporter of neoadjuvant chemotherapy in selected stage III patients, do not include this indication[ 50 ]. The Fox Chase Cancer Center guidelines comprehensively address the treatment of NSCLC during the COVID-19 pandemic stating “Patients with resectable disease can be treated with definitive non-operative management if surgical resources are limited or the risks of perioperative care are high...”[ 51 ]. Nevertheless, it is essential that the treatment approach be individualised within the parameters set by an interdisciplinary tumour board.…”
Section: Neoadjuvant and Postoperative Radiotherapy In Non-small Cellmentioning
confidence: 99%
“…Practice recommendations for lung cancer radiotherapy during the COVID-19 pandemic are provided in an ESTRO-ASTRO consensus statement by Guckenberger et al Singh et al and Dingemans et al also make recommendations on standardizing the care of lung cancer patients during COVID-19 while recommending that general standard principles of practice be followed [33][34][35]. Wu et al provide guidelines for thoracic radiation therapy specifically while Kumar et al discusses alternative management options [36,37].…”
Section: Lung Cancermentioning
confidence: 99%
“…Many researchers have proposed guidelines to manage this vulnerable population. Kumar S et al [9] suggested that in the case of limited surgical resources or high risks associated with perioperative care, NSCLC patients who presented with advanced yet localized disease that was resectable could be treated with speci c, non-surgical management, including chemotherapy, chemoimmunotherapy, radiation therapy, and immunotherapy. A previous consensus statement suggested that during the COVID-19 pandemic, the annual screening exam and treatment of clinical stage I NSCLC should be delayed [10] .…”
Section: Introductionmentioning
confidence: 99%